Associations of apolipoprotein E and low‐density lipoprotein receptor‐related protein 5 polymorphisms with dyslipidemia and generalized aggressive periodontitis in a Chinese population. (20th October 2014) - Gao, H.; Tian, Y.; Meng, H.; Hou, J.; Xu, L.; Zhang, L.; Shi, D.; Lu, R.; Feng, X.; Wang, X.; Chen, Z.
<x xml:space="preserve">Abstract</x> Background and Objective Dyslipidemia is associated with aggressive periodontitis, a condition characterized by the rapid destruction of the periodontium. Apolipoprotein E (APOE) and low‐density lipoprotein receptor‐related protein 5 (LRP5) are involved in immunomodulation and inflammatory activity. We evaluated the association of LRP5 and APOE polymorphisms with serum lipid concentrations and generalized aggressive periodontitis within a Chinese population. Material and Methods Mean serum lipid concentrations were compared across LRP5 and APOE polymorphisms, among cases (n = 185) and controls (n = 138). Multivariable logistic regression was used to evaluate the independent and combined associations of LRP5 and APOE polymorphisms with generalized aggressive periodontitis. Results Compared with controls, individuals with generalized aggressive periodontitis exhibited significantly lower serum total cholesterol (TC) and lower high‐density lipoprotein cholesterol (HDL‐c). Individuals with LRP5 polymorphisms (rs682429‐AA or rs312016‐GG) exhibited higher TC, higher HDL‐c and decreased odds for generalized aggressive periodontitis. Haplotype (A‐G), determined by rs682429 and rs312016, was also associated with decreased odds for generalized aggressive periodontitis. Furthermore, individuals with the combined polymorphisms (LRP5‐rs682429‐AA and APOE‐rs429358‐CC/CT) had higher levels of low‐density lipoprotein cholesterol, higher levels of TC and decreased odds for generalized aggressive periodontitis. Conclusion Independently or combined with APOE, LRP5 polymorphisms may lead to dyslipidemia and are associated with generalized aggressive periodontitis. Dyslipidemia may be a risk indicator for generalized aggressive periodontitis in the Chinese population. Furthermore, two LRP5 polymorphisms (rs682429 and rs312016) might be useful for identifying subjects at higher risk of generalized aggressive periodontitis.